Habitual abortion. Infectious factor. - Gonzales Enders, Rodolfo (2015)
Habitual abortion is defined as spontaneous and consecutive expulsion of at least three pregnancies up to 12 weeks. For an infectious agent can be described as common causes of abortion, it must remain alive and virulent in the host, symptomatically or not, for a long enough period of time to injure three consecutive pregnancies.